2003
DOI: 10.1002/clc.4950260703
|View full text |Cite
|
Sign up to set email alerts
|

Modulating atherosclerosis through inhibition or blockade of angiotensin

Abstract: Summary: Angiotensin-converting enzyme (ACE) inhibitors are well recognized for their benefits in treating hypertension and congestive heart failure and preventing postmyocardial infarction heart failure or left ventricular (LV) dysfunction. Recently, blockade of the angiotensin II type 1 (AT 1 ) receptor was shown to reduce cardiovascular events in hypertensive subjects with LV hypertrophy. Several lines of evidence are now converging to show that ACE inhibitors may affect the atherosclerotic process itself. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Recipient (CD45 congenic WT) mice were irradiated with 2 doses of 500 to 525 Rads, 3 hours apart, after which 8ϫ10 6 donor bone marrow cells in 200 L of PBS were injected into the femoral vein. The chimeras were kept in autoclaved cages, with 0.2% neomycin drinking water for 2 weeks, after which normal drinking water was used.…”
Section: Production Of Bone Marrow Chimerasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recipient (CD45 congenic WT) mice were irradiated with 2 doses of 500 to 525 Rads, 3 hours apart, after which 8ϫ10 6 donor bone marrow cells in 200 L of PBS were injected into the femoral vein. The chimeras were kept in autoclaved cages, with 0.2% neomycin drinking water for 2 weeks, after which normal drinking water was used.…”
Section: Production Of Bone Marrow Chimerasmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The renin-angiotensin system has also been implicated as a mediator of the deleterious consequences of the known risk factors for cardiovascular disease. For example, AT1-receptor (AT1-R) activation appears to play a major role in the development of the impaired endotheliumdependent vasodilation that is associated with hypercholesterolemia.…”
mentioning
confidence: 99%
“…An important vascular effect of ANG II is its induction of oxidative stress and a proinflammatory phenotype. Type I ANG II (AT 1 ) receptor blockade can prevent the unfavorable vascular effects by ANG II through hypertension-dependent and -independent mechanisms (1,18,22). Our previous studies have demonstrated that, in addition to vascular remodeling, elevation of circulating ANG II levels also leads to extensive microscopic myocardial repair/remodeling in both left and right ventricles in rats (21, 22).…”
mentioning
confidence: 99%
“…It is becoming increasingly accepted that Ang II, through its interaction with the AT1-R, is linked to CVD by promoting inflammation. 19,20 For example, clinical trials with AT1-R blockers show some benefit in reducing ischemic events and mortality related to CVD beyond blood pressure lowering, [21][22][23][24][25] and AT1-R antagonists inhibit LDL lipid peroxidation and development of atherosclerotic lesions in animal models of hypercholesterolemia. 26 It is well established that hypercholesterolemia elicits systemic inflammatory responses, which are characterized by an oxidative stress, elevated cytokines, and activation of blood cells.…”
mentioning
confidence: 99%